2010
DOI: 10.1149/1.3360745
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Early Stages of Oxygen Agglomeration

Abstract: The results of ab initio calculations and rate equation modeling of the early stages of oxide precipitation are compared with the results of highly sensitive FTIR spectrometry of oxygen and vacancy oxygen containing complexes in silicon after RTA treatment. The ab initio calculations have shown that the binding energy of interstitial oxygen in VO n is higher than in O n for n d 6. For higher n, the energy gain is comparable. The point defect species O 1 , O 2 , O 3 , and VO 4 were detected by highly sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Recently, it was reported that, in vacancy-rich regions of oxygen-contained silicon annealed at 700 C, there were two competitive processes: binding vacancy with interstitial oxygen forming VO n complexes (2 < n < 6) [31,32] or forming nanosized voids (noids) with dimensions about several nanometers due to vacancy coalescence. [33,34] It was noted that the noids could act as heterogeneous sites for metal impurities or as nucleation centers for OPs, but their getter efficiency was destroyed at annealing temperatures more or equal 800 C. At the same time, clusters of some VO n complexes could cause oxygen precipitation process at prolonged treatment at high temperature as well.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that, in vacancy-rich regions of oxygen-contained silicon annealed at 700 C, there were two competitive processes: binding vacancy with interstitial oxygen forming VO n complexes (2 < n < 6) [31,32] or forming nanosized voids (noids) with dimensions about several nanometers due to vacancy coalescence. [33,34] It was noted that the noids could act as heterogeneous sites for metal impurities or as nucleation centers for OPs, but their getter efficiency was destroyed at annealing temperatures more or equal 800 C. At the same time, clusters of some VO n complexes could cause oxygen precipitation process at prolonged treatment at high temperature as well.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to the effect that during RTA cooling, when the Frenkel pairs recombine again, the vacancies supersaturate. In wafers with high concentration of interstitial oxygen, the excess vacancies bind to oxygen by forming VO n complexes (5). These complexes can act as nucleation centers for oxygen precipitation (6).…”
Section: Defect Generation In Rta Pre-treated Wafersmentioning
confidence: 99%